APPLICATION OF SPECIAL EQUIPMENT AND INNOVATIVE METHOD FOR MEASURING THE ANGLE OF EXHIBITION AND SHAPE OF THE BLADE OF A BLADE COLD COLL - GANZYUK, ANDRYI; HORDIEIEV, ANATOLYI; KRAVCHUK, OLEG; KRAVCHUK, VITOR (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Forensic science, as an object of forensics, is a system of technical means, methods and techniques based on a set of scientific and technical provisions used to identify, collect, study evidence, which will contribute to the effectiveness of crime detection and investigation. The purpose of this work is to acquaint a wide range of experts with the achievements of the team of authors and to consider the possibilities of developing and implementing new domestic tools for photofixation and innovative way to determine the angle and shape of the blade, as one of the technical characteristics of bladed melee weapons. research. The successful conduct of forensic research largely depends on the state of development of their theoretical foundations and technical equipment, which is the basis for practical activities. That is why at present the study of current problems of methodology and technical organization of the examination of bladed melee weapons is becoming more important. The experience of application of various technical means and methods of measuring the sharpening angle of the blade is analyzed, the search for analogues is carried out, the shortcomings of the available equipment are established and the value of sharpening angle measurement error is estimated in different ways. A patent search of the database was conducted, which revealed the opportunities and shortcomings of existing technical solutions. It is established that from practical experience there are different forms of sharpening at the intersection of the blade of a cold weapon. The main dimensional characteristics and structure of the blade and its individual elements are analyzed. An innovative method with the use of modern innovative equipment for determining the angle of sharpening and angles of inclination of the blade using modern CAD software products on a personal computer is proposed. Describes the design of equipment for photography when lighting the object of study from below. As an example of application of the offered method of measurement the process of step-by-step actions of the expert at carrying out expert researches of the cold blade weapon and results of definition of an angle of sharpening and angles of inclination of a blade of a sample is resulted.